Pengembangan bahan ajar menggunakan software articulate storyline 3 pada materi konsep manajemen - Siti Nur Rohmah; Nadia Fikrotun Nisa' (Universitas Hamzanwadi, 2022)
Teaching materials are generally used as a reference in supporting the learning process because they consist of learning materials that play an important role in helping learning activities. The development of knowledge and technology makes teaching materials develop in various forms and types, one of which is technology-based teaching materials. The presence of teaching materials must be an alternative in order to solve problems in the classroom. This study aims to develop interactive learning media about Management Concepts This teaching material was developed because there were various learning problems experienced by students at SMA Tuban. These teaching materials are compiled through the Articulate Storyline 3 application software with research and development methods through the ADDIE approach (Analyze, Design, Development, Implementation, and Evaluation). It is known that the results of the trials that have been carried out have shown that the teaching materials developed meet the appropriate criteria. Through the preparation of these teaching materials, the writer hopes that students can learn independently in the current era of educational technology, then can increase the enthusiasm of students' learning so that they can realize the value of satisfying learning outcomes.